Users satisfaction toward learning space services quality at Tunku Tun Aminah Library (Technical University's Library): A case study - Muhamad Saufi Che Rusuli; Norlizawati Yusof; Safiee Idris; Rosmaini Tasmin; Norazlin Hashim; Sphend Imeri (Science Publishing Group, 2015)
Academic libraries are known as major contributors to students learning on campus, thus, as an important department within higher education institutes and the informal learning space is not known much these days. Therefore, this study strives to discuss about learning space service quality toward user satisfaction at the Tunku Tun Aminah Library (Technical University’s Library). Indeed, it is of high importance to determine how the change in space impacts library users such as ‘students’ perception’ of the learning space which incorporates elements. These identified elements of providing normal learning space mainly consist of ventilated facilities, lighting, size, sound effect, colors and furniture. Hence, this study utilized survey as an instrument and randomly distributed to 339 students who have used the library. The data were analyzed by Rasch measurement model (WINSTEP 3.69.1.11) and the results show that library users’ were moderatley satisfied with learning space (i.e. Iqra’ Room) provided by the library.